Bevacizumab in recurrent WHO grades II–III glioma - Annakib, Soufyan; Rigau, Valérie; Darlix, Amélie; Gozé, Catherine; Duffau, Hugues; Bauchet, Luc; Jarlier, Marta; Fabbro, Michel (Frontiers in Oncology, 2023)
The management of recurrent WHO grade II-III (rGII-III) glioma is not well established. This study describes the clinical outcomes in patients who received bevacizumab as rescue treatment.In this retrospective study, the main inclusion criteria were as follows: adult patients with histologicaly proved rGII-III glioma according 2016 WHO classification treated with bevacizumab from 2011 to 2019, T1 contrast enhancement on MRI. Efficacy was assessed using the high-grade glioma 2017 Response Assessment in Neuro-Oncology criteria. Progression-Free Survival (PFS) and Overall Survival (OS) were estimated using the Kaplan-Meier method.Results: Eighty-one patients were included (M/F ratio: 1.7, median age at diagnosis: 38 years) among whom 46 (56.8%) had an initial diagnosis of grade II glioma. Previous treatments included at least one surgical intervention, radiotherapy (98.8%), and ≥2 chemotherapy lines (64.2%). After bevacizumab initiation, partial response, stable disease and progressive disease were observed in 27.2%, 22.2% and 50.6% of patients. The median PFS Bevacizumab in recurrent low-grade glioma 2 and OS were 4.9 months (95% Confidence Interval (CI) 3.7-6.1) and 7.6 months (95% CI 5.5-9.9). Bevacizumab severe toxicity occurred in 12.3%. Twenty-four (29.6%) patients discontinued bevacizumab without radiological progression. Oligodendroglioma and age ≥38 years at diagnosis were more frequent in this subgroup (Odds Ratio=0.24, p=0.023 and 0.36, p=0.042). Ten of these 24 patients were alive at 12 months and two patients at 8 years after bevacizumab initiation, without any subsequent treatment.Bevacizumab can be an option for heavily pretreated patients with rGII-III glioma with contrast enhancement. In our study, bevacizumab displayed prolonged activity in a subgroup of patients.